ANALISIS OVERALL EQUIPMENT EFFECTIVENESS PADA BARGE LOADING CONVEYOR (BLC) PT MITRA BARITO - Noveriady; Mindo Tiorida Panjaitan; Novalisae (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
A barge loading conveyor (BLC) is the main means of transporting coal (material handling) from the stockpile to the barge. Disruption of the conveyor which is driven by an electric motor results in the cessation of the coal shipping process, so performance and efficiency in its use must be ensured. The purpose of this research is to see the value of overall equipment effectiveness (OEE) on PT Mitra Barito barge loading conveyor (BLC), which will later be used as a basis for corrective actions and efforts to increase productivity. The method used in this research is a quantitative method where at this stage the value of overall equipment effectiveness (OEE) is calculated which includes three categories of levels of availability, level of performance, and level of quality. Where in looking at the causes of low OEE seen from the proportion of six major losses. The results showed that the average overall equipment effectiveness (OEE) value of 56.19% was considered ineffective because corrective steps still needed to be taken so that it could inhibit barge loading conveyor (BLC) activities. This is affected by slowdowns, tuning, and adjustments, as well as idling and mining stops with high loss proportion values.